2020
DOI: 10.1016/j.athoracsur.2019.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of the Fontan Operation for Patients With Heterotaxy: A Meta-Analysis of 848 Patients

Abstract: Background. Heterotaxy is considered a risk factor for adverse events at all stages in the pre-Fontan pathway, and Fontan outcomes are expected to be worse in patients with heterotaxy. The aim of this study was to review existing literature reporting outcomes of the Fontan operation systematically in patients with heterotaxy.Methods. A systematic review and meta-analysis was performed to identify and synthesize early mortality and medium-and long-term survival in heterotaxy patients after the Fontan procedure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 47 publications
3
19
3
Order By: Relevance
“…This study reviewed our experience in the management of 86 patients with atrial isomerism in our center over the past 13-years. Our data showed that despite even greater clinical diversity, the intermediate outcomes were improving, and 10year survival rate reached 79.3%, which is comparable to many of the previous reports (5,6). Consistent with previous studies, we found that extracardiac TAPVC, more than moderate AVV regurgitation, and requirement for first-stage palliative surgery were independent risk factors for mortality.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study reviewed our experience in the management of 86 patients with atrial isomerism in our center over the past 13-years. Our data showed that despite even greater clinical diversity, the intermediate outcomes were improving, and 10year survival rate reached 79.3%, which is comparable to many of the previous reports (5,6). Consistent with previous studies, we found that extracardiac TAPVC, more than moderate AVV regurgitation, and requirement for first-stage palliative surgery were independent risk factors for mortality.…”
Section: Discussionsupporting
confidence: 91%
“…Cardiovascular mortality in early childhood is estimated at about 10% or more, even in the current era (2,3). Fortunately, recent reports from developed countries showed that the survival of atrial isomerism with cardiac malformation is continuing to improve, and most patients can survive into adulthood (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] In addition, in our cohort of patients an associated syndrome did not increase the mortality and the survival of our cohort of patients with heterotaxy did not differ from that published in a recent meta-analysis. 11 Our study suggests that the presence of a genetic syndrome in association with single-ventricle AVSD does not preclude an excellent outcome for Fontan palliation.…”
Section: Discussionmentioning
confidence: 63%
“… 5) Studies have indicated that early mortality after the Fontan procedure is higher in heterotaxy patients, but the long-term survival is comparable to the overall Fontan population. 12) …”
Section: Anatomy Of the Fontan Circuitmentioning
confidence: 99%